Ethanol Production by Fermentation of Various Sweet-Stalk Sorghum Juices Using Various Yeast Strains - Widianto, Donny; Arofatullah, Akbar; Yuwono, Triwibowo; Prijambada, Irfan Dwidya (Indonesian Journal of Biotechnology, 2010)
The ethanol production by fermentation of sweet-stalk sorghum juice is affected by the juice composition and the capability of the yeast strain to ferment it. Eight yeast strains were tested on their growth and ethanol fermentation abilities in sweet-stalk sorghum juices extracted from three cultivars of sweet sorghum. The best specific growth rate of the yeast strains grown aerobically in the yeast extract peptone dextrose (YEPD) broth and the sweet-stalk sorghum juices of KCS105, FS501, and FS902 cultivars, were achieved by OUT7903, OUT7913, OUT7903, and OUT7027 yeast strains, respectively. However, the best specific CO2 evolution rate of the yeast strain during fermentation of the juices was achieved by OUT7027 yeast strains. The highest ethanol concentration, ethanol yield, and sugar conversion efficiency (SCE) were obtained by strain OUT7921 when it was employed to ferment sweet-stem sorghum juice of FS902 cultivar. It was also observed that the juice extracted from sweet-stalk sorghum of FS902 cultivar is the most suitable medium for all yeast strains to achieve their best fermentation abilities. Thus, it is likely that the growth and ethanol production ability of a yeast strain in sweet-stalk sorghum juice depend on the physiological responses of the yeasts to nutrientcomposition of the sorghum juice and the sorghum cultivar from which the juice was extracted.Key words : Sweet-stalk sorghum juice, ethanol, fermentation, yeast